2021
DOI: 10.2478/bsrj-2021-0032
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Value and Growth Stocks in the Aftermath of the Global Financial Crisis

Abstract: Background: Due to strong empirical evidence from different markets, existence of value premium became a financial theory standpoint. Although previous studies found that value stocks beat growth stocks in bearish and bullish markets, during the GFC, value stocks underperformed growth stocks. Objectives: This paper aims to examine the performance of value and growth stock portfolios after the GFC. Subjects of our analysis are constituent companies of the DJIA index, out of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The result was the opposite for the consumer products and services sector, which saw an increase to 30%. The percentage of the technology sector was 10% in growth stocks, which had no significant representation in value stocks since the majority of growth stocks are a part of the technology sector (Bevanda et al, 2021). The technology sector is characterised by the greater potential for growth in the future The dominant sectors in growth stocks are consumer products and services, which include, in Bursa Malaysia, agricultural products, consumer services, food/beverages, travel, hospitality, etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result was the opposite for the consumer products and services sector, which saw an increase to 30%. The percentage of the technology sector was 10% in growth stocks, which had no significant representation in value stocks since the majority of growth stocks are a part of the technology sector (Bevanda et al, 2021). The technology sector is characterised by the greater potential for growth in the future The dominant sectors in growth stocks are consumer products and services, which include, in Bursa Malaysia, agricultural products, consumer services, food/beverages, travel, hospitality, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Value stocks did not beat growth stocks until the years before 1994 and the years before the GFC, and even then, the gap between growth and value stocks was insignificant. Besides, Bevanda et al (2021) found that growth stocks now outperform value stocks, as evidenced by financial theory and investment management implications since 2009. Causes could include (1) an expansionary monetary policy with very low long-term interest rates and (2) the tech industry's strong success, which the majority of growth stocks are a part of.…”
Section: Annual Return Of Value and Growth Stocksmentioning
confidence: 97%
“…Undervalued securities have historically produced an independent source of risk which has diversification benefits in portfolio management as well as risk management. Market research on US value premium stocks have been well documented in prior literature (Jeong, Lee & Mukherji, 2009;Athanassakos, 2009;Bevanda & Arnaut -Berilo, 2021) as well as evidence that anomalies in stock markets exist and tend to disappear or decline once they are published (Enow, 2022;. Therefore, theorising observations on undervalued stocks that have outperformed other securities is not the core of financial theory and is really not helpful in isolation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given that the economic crisis caused by the COVID-19 pandemic is still ongoing, it offers vast opportunities for scientific activities. Hence, various economic variables should be considered in future research to enhance the understanding of its effect on the corporate environment [47], and to identify the means necessary for timely and effective response to its consequences [48].…”
Section: Future Research and Research Limitationsmentioning
confidence: 99%